The Creation of a Japanese Prisoner of War Camps in Central Asia - Kasimxo’jaevich, Nazirxo’jaev Muhammadalixo’ja (International Journal on Integrated Education, 2023)
The article provides an analytical overview of the reasons for post-World War II prisoners of war in camps in Central Asia and Uzbekistan, the conditions of the camps, and the involvement of prisoners of war in the national economy. In order to keep prisoners captive, the General Directorate of risoners will be established within the Interior. The deployment of prisoners of war across the former Soviet Union was uneven. There were more camps and, of course, more prisoners of war in areas where destruction was the result of the war. They did this under the convoy control[4]. Japanese prisoners of war worked in less favorable weather conditions in Uzbekistan than in the cold climatic zones of the northern and eastern parts of the former Soviet Union. Apart from these camps there was an evacuation hospital No. 1054. Military camps are organized in the regions of Kazakhstan, such as Aktyubinsk, Almaty, East Kazakhstan, Karaganda, Kyzyl-Orda and Shymkent. Even in the early postwar years, prisoner camps were often ineffective in recruiting prisoners for labor, and for failing to meet the standards of labor, due to the lack of skills of officers and guards who were hired to oversee them. During the last years of the war, the mortality rate among prisoners has increased in the early years due to the dramatic increase in prisoners in the camps, their out-of-state combat and transported to camps with disease on the road, and insufficient sanitation..